HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR PADA MAHASISWA PSKPS FK ULM TINGKAT AKHIR DALAM PENGERJAAN SKRIPSI - Nurhaliza, Berliana; Fadillah, Syaiful; Wasilah, Siti; Fitria, Yanti; Muthmainah, Noor (Homeostasis, 2023)
Stress is something that can be caused by an imbalance between expectations and reality that individuals desire, both physically and mentally. Sleep contributes to maintaining physiological and psychological conditions. Poor sleep quality can be caused by various things such as sleep disturbances when a person sleeps. Emotional stress can cause feelings of tension and can make it difficult for individuals to sleep. At times of stress there is an increase in the hormones epinephrine, norepinephrine and cortisol which affect the central nervous system and cause a state of wakefulness and increase the alertness of the CNS system. This study aims to determine the relationship between stress levels and sleep quality in PSKPS FK ULM students with a total of 153 students. where 67 people were taken as a sample by random sampling technique. Data collection was carried out using the DASS42 questionnaire and the results obtained were a mild stress level of 17.9%, a moderate stress level of 40.29%, a severe stress level of 28.35% and a very severe stress level of 13.43%. In the PSQI, the results of good sleep quality were 11.94% and 88.05% poor sleep quality. The results of the statistical test using the Spearmen Rank with α = 0.05 obtained a value of p = 0.403 which is positive, indicating a weak and one-way relationship so that it can be concluded that there is a relationship between stress levels and sleep quality in PSKPS FK ULM final year students in their thesis work.